Insecticidal and repellant activities of selected botanical extracts against rice weevil (Sitophilus oryzae L.) - Ali Albariman, Najm Hussein (2020)
Stored rice is infected primarily by adult rice weevil (Sitophilus oryzae L.). Botanical pesticides could be alternatives to synthetic insecticides due to their effectiveness and lower toxicity. This study investigated repellence activity, insecticidal activity and phytochemical composition of acetone and ethanol extracts of basil leaves (Ocimum basilicum), turmeric leaves (Curcuma longa) and akar mempelas stem (Tetracera macrophylla) against adult rice weevil (Sitophilus oryzae L.) on stored rice. Methodology involved preparing 0%, 10%, 20% and 30% concentrations of either ethanol or acetone extract of each plant to be examined for their repellence activity, contact toxicity and phytochemical composition using gas chromatography-mass spectroscopy (GC-MS). Results showed that acetone and ethanol extracts of the three plants exerted dose-dependent repellence and time-dependent contact toxicities. Ethanol extracts of the three plants showed superior repellence activity and contact toxicity were superior to those of their acetone extracts, while the repellence activity and contact toxicities of the ethanol and acetone extracts of basil were superior to those of turmeric and Akar mempelas. GC-MS indicated that basil acetone extract contained anethole, while the ethanol extract contained bis (2-Ethylhexyl) phthalate. Turmeric acetone extract contained Ar-turmerone, while the ethanol extract contained bis(2-Ethylhexyl) phthalate. Akar mempelas stem acetone extract contained 1-tetradecene, while the ethanol extract contained 1-octadecene and bis(2- Ethylhexyl) phthalate. In conclusion, acetone and ethanol extracts of basil leaves, turmeric leaves and akar mempelas stem exhibited effective dose-dependent repellant activities and time-dependent insecticidal activities against the adult rice weevil. However, the repellant and contact toxicity of ethanol extracts of the basil, turmeric and akar mempelas were superior to those of their acetone extracts, while the repellence and contact toxicities of the ethanol and acetone extracts of basil were superior to those of turmeric and akar mempelas.